The Effect of Dielectric Barrier Discharge (DBD) Plasma on the Inhibition of Enterococcus Faecalis and Streptococcus Mutans - Abdullah, Khnsaa; Kadhem, Saba J. (Iraqi Journal of Physics, 2025)
This study investigates the effect of Dielectric Barrier Discharge (DBD) plasma on the inhibition of bacterial growth. The DBD plasma system operates with a high-voltage power supply at a frequency of 8.4 kHz and an AC voltage of 20 kV. The study utilized two strains of pathogenic gram-positive bacteria, Streptococcus mutans and Enterococcus faecalis. The bacterial species were split into two groups at two distinct dilution levels (108). Following a series of dilution steps ranging from 101 to 109. The bacteria were subjected to DBD plasma treatment for different durations (0.5, 1, 1.5, 2, and 2.5 min). The Dielectric Barrier Discharge (DBD) plasma treatment resulted in a statistically significant increase in bacterial death (P < 0.05) compared to the control group. Exposure to DBD plasma effectively resulted in bacterial kill; longer treatment durations yielded greater bacterial inactivation. These results demonstrated the potential of DBD plasma in clinical and environmental applications for bacterial control.